CATALYTIC GASIFICATION OF OIL PALM EMPTY FRUIT BUNCH BY USING INDONESIAN BENTONITE AS THE CATALYST - Aprianti, Nabila; Faizal, Muhammad; Said, Muhammad; Nasir, Subriyer (Journal of Applied Engineering Science, 2021)
Oil palm empty fruit bunch (OPEFB is one of the enormous waste expected to become a renewable energy source. This study aimed to convert OPEFB into syngas through a gasification process using bentonite as a catalyst. The effects of temperature and product gas catalysts were investigated, and the efficiency of the gasification process was summarized. The process has used an updraft gasifier at 350-550 °C and air as the gasification medium (ER 0.2). The results indicate that syngas can be produced by updraft gasifier. When the temperature increase, the H2 and CO rising. The highest H2 and CO content of 27.74% and 20.43% are obtained at 550°C when bentonite applied. HHV and LHV range of 3.38 12.79 MJ/Nm3 and 3.03 11.58 MJ/Nm3, respectively. The maximum carbon conversion efficiency (CCE) and cold gas efficiency (CGE) reach 85.49% and 82.34%. Bentonite has been able to increase the concentration of the gas composition especially H2 and CO and the heating value of syngas.